2020
DOI: 10.1007/s40745-020-00305-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Artificial Neural Network Architectures for Brazilian Stock Market Prediction

Abstract: Prediction of financial time series is a great challenge for statistical models. In general, the stock market times series present high volatility due to its sensitivity to economic and political factors. Furthermore, recently, the covid-19 pandemic has caused a drastic change in the stock exchange times series. In this challenging context, several computational techniques have been proposed to improve the performance of predicting such times series. The main goal of this article is to compare the prediction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…On the other hand, logistic regression is utilized for binary outcomes, estimating the probability of a categorical event occurring, such as the likelihood of loan defaults or the probability of credit risk. Logistic regression works by applying a logistic function to the linear combination of the input variables, thus transforming the output into a probability value between 0 and 1, making it ideal for classification tasks in financial risk assessment (de Pauli et al, 2020). These models are crucial in various financial applications due to their simplicity, interpretability, and effectiveness.…”
Section: Linear Regression and Logistic Regressionmentioning
confidence: 99%
“…On the other hand, logistic regression is utilized for binary outcomes, estimating the probability of a categorical event occurring, such as the likelihood of loan defaults or the probability of credit risk. Logistic regression works by applying a logistic function to the linear combination of the input variables, thus transforming the output into a probability value between 0 and 1, making it ideal for classification tasks in financial risk assessment (de Pauli et al, 2020). These models are crucial in various financial applications due to their simplicity, interpretability, and effectiveness.…”
Section: Linear Regression and Logistic Regressionmentioning
confidence: 99%
“…Popular theories suggested that the stock markets required a random walk; in most conventional time series, prediction methods were dependent on stationary trends; therefore, the stock price prediction was inherently tricky 11 . Moreover, the stock price prediction was challenging due to the more significant number of involved variables 12 . Moreover, machine learning (ML) is the most powerful tool that includes various algorithms to develop their performance effectively 13 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, the stock price prediction was challenging due to the more significant number of involved variables. 12 Moreover, machine learning (ML) is the most powerful tool that includes various algorithms to develop their performance effectively. 13 In general, ML can obtain detecting patterns and valid information from the dataset.…”
mentioning
confidence: 99%
“…Deep learning hierarchical models such as convolutional neural network (CNN) [ 13 ], recurrent neural network (RNN) [ 14 , 15 ], long short term memory (LSTM) [ 16 ] and recurrent convolutional neural network (RCNN) [ 17 ] are capable for finding the hidden features through a self learning process. The performance of five neural network architectures such as multi-layer perceptron (MLP) network, elman neural network (ENN), jordan neural network (JNN), radial basis functions neural networks (RBF), and multiple linear regression (MLR) to predict the six most traded stocks of the official Brazilian stock exchange during the Covid-19 period is compared in [ 18 ]. Their analysis concluded that these models provide reasonable predictions and thus can be used as support models for the companies.…”
Section: Introductionmentioning
confidence: 99%